Cyberlearning the learning management system and the influence of its usage on student engagement - Mandap, Marco C. (2019)
With the integration of the internet into the teaching system, education today has rapidly evolved into cyber learning. Consequently, several educational institutions have adopted learning management systems (LMS), a comprehensive digital platform, to facilitate online instruction. The present study seeks to measure extent of the influence of LMS usage on student engagement. The variables of the study were quantified using instruments with a five-point Likert scale as a response. A total of 190 students enrolled at a host institutions in Manila comprised the respondents of the study. Using G* Power Analysis at an assumed effect size of Cohen's f-squared=0.15, the researcher computed the sample size. Results reveal that the use of an LMS influences student engagement significantly. Furthermore, the students work at their studies beyond the moderate extent of LMS usage. The data suggest that messaging students and setting schedules in the LMS increase their engagement on the platform. However, the components of announcements, discussions, and people negatively affect their level of engagement. The study highly recommends that the information dissemination through the LMS should be re-designed in such a way that it more directly motivates students. This research also highlighted that LMS discussions tend to become interactive. The findings and conclusions urge that socialization should feature inside the LMS.
Keywords: Digital technology; Alternative education; Learning; Student performance; Levels of engagement; Student interests; Computer-assisted collaborative learning; Online learning; Usage; Students